Speed control of BLDC motor using PID controller - Ramu, Tirunagari Bhargava; Cheerla, Sreevardhan; Kallakuta, Ravi Kumar; Mohan, Kaja Krishna; Inthiyaz, Syed; Prakash, Nelaturi Nanda; Rajanna, Bodapati Venkata; Kumar, Cheeli Ashok (International Journal of Applied Power Engineering (IJAPE), 2025)
The current state of science, technology, and industrial revolutions did not occur overnight. Many years of empirical study attempts by human intelligence have led to the world's current status. As a result, new technologies and innovations would constantly propel human civilization forward. Another outstanding invention of the present day is the brushless DC (BLDC) motor. This paper outlines the design of a BLDC motor control system utilizing MATLAB/Simulink software. The main aim of this project is to control the speed and to obtain time domain specifications of PID controller. The application of speed control of motor is vast and also required to maintain the work efficient without any disturbance, the power consumption, and any other fuel to run. On the basis of this the brushless DC motor as application is selected because of reduction in losses and also the power. The PID control system is built to control the speed of the motor and gives the precise output. The universal bridge is used to amplify the current in the output of the application. PID controller reduces the error and increases the stability of the system.